『중국학보』전근대 중국사논문 서평: 한국학계 중국사 연구 60년사 ― 연구 영역의 확대와 주제의 심화 - 김선민; Kim Seonmin (중국학보, 2022)
본 서평은 1963년부터 2021년까지 발표된 180여 편 논문들의 연구 경향과 추이를 분석한다. 먼저 1963년에 발간된 1집부터 1999년에 발간된 39집까지의 논문을 한국학계 중국사 연구의 초기 단계로 파악하고, 이 시기에 출판된 50여 편의 논문들에서 나타나는 특징을 “원로 선학들의 연구”, “한중관계사 연구”, “해외 학계의 영향”으로 나누어 소개한다. 이어 2000년 이후에 발간된 41집부터 99집까지 출판된 130여 편의 논문을 최근 연구로 분류하고 여기에서 보이는 중국사 연구의 새로운 동향을 고고학 자료의 활용, 주제의 세분화와 정밀화, 그리고 북방 유목 세계에 대한 연구의 심화를 통해 살펴본다. 또한 한중관계사 분야 역시 단지 중국으로부터 한국에 전해진 단선적인 영향을 확인하는 연구에서 벗어나 양측의 상호 작용, 그리고 중국 문화의 복잡성을 설명하는 단계로 발전했음을 지적한다. 한국학계의 중국사 연구는 과거에는 접할 수 없었던 새로운 사료를 활용하여 연구 영역을 확장하고 있으며, 국내외 학계의 오랜 연구 주제를 더욱 심화하여 전문화하고 있다. 나아가 중국학에서 오랫동안 소외되었던 주변부에 대한 관심이 커지고 한중관계에 대한 연구가 쌍방향으로 다각화되는 등 괄목할만한 성장을 보여주고 있다. This paper examines the Korean scholarship of the field of premodern Chinese history during the past sixty years by analyzing about 180 articles published in the Chung Kuk Hak Po during the periods from 1963 to 2021. It explains the years from 1963 to 1999 as the early stage of Chinese Studies in Korea, while the past twenty years since 2000 are discussed as the recent stage of Korean academia. Comparing the articles of the Chung Kuk Hak Po published before and after the year 2000, this paper addresses that Korean research achievements on Chinese history have showed a remarkable growth both in quality and quantity. Recently many Korean scholars have expanded their research topics and scopes by using archaeological evidence and various language materials, a new source that had not been available for the early generation of Korean scholars. At the same time, more specialized questions have been explored in each period of Chinese history. One of the most notable changes in recent studies is increasing scholarly interests in Inner Asian frontiers, a place where has received little attention earlier in Korean academia. We hope that the Chung Kuk Hak Po will continue to make its dedication and contribution to future development of Chinese Studies in Korea.